Investigating the adsorption method using polymer nanocomposites as adsorbent to remove organic pollutants: A review - Ali Hosseinian Naeini (Journal of Applied Research in Water and Wastewater)
It is becoming increasingly evident that numerous nations are teetering on the edge of a crisis induced by environmental issues, posing threats to the well-being of both humans and animals. Diverse factors characterized by vivid hues, like air pollution and fluctuations in water quality, contribute to a multitude of issues and can adversely impact the environment at large. Given the current heightened demand for freshwater reserves, there exists a more urgent necessity to devisepragmatic approaches for treating wastewater. One prospective technique entails the utilization of polymer nanocomposites to avert impurities such as heavy oils, cosmetics, and oil-based paints. These adjuncts leverage state-of-the-art nanotechnologies, such as carbon nanotubes and activated carbon, showcasing significant efficacy in refining water resources. Concurrently, striking a balance between financial viability and environmental benevolence. Moreover, the employment of adsorption methodologies proves to be highly efficacious in decontaminating tainted water reservoirs by eradicating organic pollutants, employing an array of substances as adsorbents for this purpose. Exemplars of thriving adsorbents include dendritic polymers MXenes, which manifest distinctive characteristics like heightened surface area and porosity, coupled with enhanced reusability and structural integrity when amalgamated with polysaccharides. Generally, the application of polymer nanocomposites as adsorbents for organic contaminants holds promising potential in innovating novel, cost-effective techniques for purifying water and shielding against chemical impurities.